PENGARUH MODEL PLTL TERHADAP KEMAMPUAN PEMAHAMAN KONSEP PADA MATERI TATA NAMA SENYAWA - Ayu Rahayu; Alimuddin Alimuddin; Musdalifatul Adewia (Prima Magistra: Jurnal Ilmiah Kependidikan, 2023)
Understanding the concept is an ability that has an important role in the learning process so that students' conceptual understanding can be developed which is considered capable of representing abstract chemical concepts. This study aims to determine the influence and responses of students related to the application of the PLTL (peer led team learning) model on the ability to understand concepts in the nomenclature material for class X SMAN 1 Latambaga compounds. In this study, descriptive tests, questionnaires, and observation sheets were used as instruments in this study. The type intended in this study is Quasi Experimental Design by way of Posttest-Only Design. A total of 35 students were used in the class with the peer led team learning (PLTL) treatment applied in this case the experimental class (X MIPA 1), and 35 students were used in the class without treatment in this case the control class (X MIPA 2). The research results were obtained through the experimental class with an average value of 44.51. However, the control class produced an average of 26.11. To test the hypothesis using the IBM SPSS Statistics 26 it is significant with a value of 0.000 <0.05 meaning that H0 is rejected and H1 is accepted. So that it can be concluded that there is an influence of the PLTL (peer led team learning) model on the ability to understand concepts in nomenclature material for class X SMAN 1 Latambaga.